The Level of Future Time Perspective among Tishreen University Students in the Light of Some Variables - Sobh, Safaa; Zyzafoon, Abeer (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The purpose of this study was to determine the level of Future Time Perspective among Tishreen University Students, as well as the differences in their future time perspective according to the variables: gender, college and university year. The sample of the study consisted of (393) students: (121) males and (272) females, distributed over the first year and the graduation year, in the faculties of theoretical and applied. To achieve the aim of the study, the researcher used the descriptive research methodology, and the measure of future time perspective (prepared) which consists of (23) items. The study showed the following results: the level of future time perspective among Tishreen University students is high. There are no statistical significant differences in future time perspective among the sample members according to gender and college. while there were statistical significant differences in future time perspective among the sample members according to university year in favor of the graduation year students. هدف البحث إلى تعرف مستوى المنظور المستقبلي لدى طلبة جامعة تشرين, وكذلك تعرف الفروق في المنظور المستقبلي لديهم تبعاً لمتغيرات الجنس, والكلية, والسنة الدراسية. تكونت عينة البحث من (393) طالباً وطالبة, منهم (121) طالباً, و(272) طالبة موزعين على السنة الدراسية الأولى وسنة التخرج, يمثلون فروع كليات الدراسة النظرية والتطبيقية. ولتحقيق هذه الأهداف اتبعت الباحثة منهج البحث الوصفي, واستخدمت مقياس المنظور المستقبلي (من إعداد الباحثة) والذي تكون من (23) بنداً. وأظهرت الدراسة النتائج التالية: - مستوى المنظور المستقبلي لدى طلبة جامعة تشرين مرتفع. - لا توجد فروق ذات دلالة إحصائية في المنظور المستقبلي لدى أفراد عينة البحث تبعاً لمتغيري الجنس والكلية. - بينما وجدت فروق ذات دلالة إحصائية في المنظور المستقبلي لدى أفراد عينة البحث تبعاً لمتغير السنة الدراسية لصالح الطلبة في سنة التخرج.